The role of sex hormones in physiological adaptation and athletic performance in women with hyperandrogenism: medical and ethical aspects - Kępczyńska, Aleksandra; Górecki, Kamil; Prokop, Przemysław; Barszczewski, Konrad; Korzonek, Urszula (Quality in Sport, 2024)
Introduction: Hyperandrogenism in women's sports is a topic that has been controversial for years and has been discussed and debated internationally. It concerns the participation of women with elevated testosterone levels in sports competitions, especially in disciplines where physical strength and performance are crucial. Gender categorization in sports has a biological basis and stems from significant physiological differences between men and women. The aim: To ensure fair competition and equal opportunities for all participants. Materials and methods: A systematic review explored the link between androgen levels and athletic performance improvement. Google Scholar and PubMed were searched in polish and english language. Results: The issue of hyperandrogenism in sports often arises in the context of controlling the fairness of competition. Many researchers and sports activists argue that high levels of testosterone can give an unfair advantage, especially in sports requiring strength and speed. Therefore, the International Olympic Committee (IOC) and other sports organizations have introduced limits on testosterone levels in women competing in certain sports. It is also worth noting that hyperandrogenism is not always due to doping or unfair practices. Often it is a physiological condition that can result from individual genetic characteristics. The approach to this issue requires consideration of both aspects of fair competition and the rights of athletes to compete without discrimination based on their natural physiological characteristics.